Nivel de satisfacción en las usuarias que se realizan el control prenatal en el Centro de Salud N° 3 de la ciudad de Loja. - Veintimilla Aguirre, Byron Patricio (2013)
The study was performed in order to describe the view that pregnant women have regarding the quality of care they receive at the health center which was developed based on the objectives which analyzes presented three variables which based on the analysis of the infrastructure that the health center has also analyzed the processes performed in if as is the waiting time and the treatment by the physician and the third variable was used to analyze the result of the processes allowing us to determine the quality of care provided by the Health Center No 3 of the city of Loja , for which we have used the User satisfaction Survey of Health Services is the same as standardized by the Ministry of Public Health of Ecuador , to carry out the analysis of the variables involved; having made ​​it as a method of data collection , review of the statistics presented by the Provincial Health department Loja in statistics. Then he proceeded to review the literature that the same constitutes a summary of concepts and information that serves as theoretical basis for practical work to be executed later. Below are the results of practical work , using statistical charts which discusses the variables to study in which we observe in what regards infrastructure by the health post, find the highest point in terms of opinion of users in the identification by health personnel with 78 % followed by the toilet presented by the various areas of the site that reach an average of 72 % in relation to the care process we conclude that the high point is found in respect for the privacy of users by the doctor with a 100 % , as well as the answers to the questions raised by the users with 92 % , the main problem encountered during the process of care was presented as dissatisfaction the perspectives of users is the delay time for care the same as at 56% I think they should wait between 1 and 2 hours , as to the result of the process is provided in the home care health found that 83 % of clients who were surveyed are satisfied with the quality of services that we find it flattering as it gives us to denote the knowledge and quality of service provided , in terms of the organization provided by the health post find some degree of dissatisfaction expressed by 56 % of users , we also determine the level of confidence on the part of users to health services found that there is a 70 % confidence index , based on these findings was further relevant recommendations presented the literature of which yielded the respective theoretical framework consulted, and the construction of an index for understanding the contents of this thesis , and finally , the necessary annexes thereof. KEYWORDS Quality , Satisfaction , Trust, Care Processes, Health .